2013
DOI: 10.1007/s11255-013-0406-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic potential of ERG (ETS-related gene) expression in prostatic adenocarcinoma

Abstract: Purpose Following patients after prostatectomy can be expensive and stressful, therefore, a novel and reliable approach to improve stratification is needed both at diagnosis of PCa and following its treatment. We evaluate the association of both ERG and claudin-4, -5 and betacatenin expression in tumor tissues of patients with organ confined and advanced prostatic adenocarcinomas. Methods A total of 30 patients were included in the study. Nine men, who underwent radical prostatectomy for organ confined (pT2N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…While a significant association was also observed between ERG-negative index tumor status and metastatic progression, very few patients developed metastasis (n = 40; median follow-up time = 5 yr); therefore, these data are not included in this report. Both positive and negative correlations between ERG status and CaP outcomes have been reported in literature, likely due to cohort selection, as exemplified in this study, showing a potential interaction of age, race, obesity, tumor molecular subtype (ERG-positive or ERG-negative status), and other as-yet-unknown potential biological factors [28]. Interactions of ERG and obesity are also not clear due to apparent discrepancies between two studies [21,24].…”
Section: Discussionmentioning
confidence: 60%
“…While a significant association was also observed between ERG-negative index tumor status and metastatic progression, very few patients developed metastasis (n = 40; median follow-up time = 5 yr); therefore, these data are not included in this report. Both positive and negative correlations between ERG status and CaP outcomes have been reported in literature, likely due to cohort selection, as exemplified in this study, showing a potential interaction of age, race, obesity, tumor molecular subtype (ERG-positive or ERG-negative status), and other as-yet-unknown potential biological factors [28]. Interactions of ERG and obesity are also not clear due to apparent discrepancies between two studies [21,24].…”
Section: Discussionmentioning
confidence: 60%
“…Also, they failed to see ERG expression in PIN. Szasz et al in a small study [14] found a positive correlation between ERG expression and Gleason grade; they also observed more ERG-positive cases in advanced cancers than in prostate-confined ones. These results are very similar to the relationships seen in our material.…”
Section: Discussionmentioning
confidence: 92%
“…The prognosis of patients with clinically aggressive pancreatic cancer cannot be accurately predicted by standard variables such as pathologic stage; thus other biomarkers are needed. Expression of transcription factors associated with metastasis have shown promise as prognostic biomarkers ( 25 , 26 ). Little is known, however, regarding the expression of transcription factors involved in the processes regulating invasion and metastasis in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%